The effect of linguistic experience on perceived vowel duration: Evidence from Taiwan Mandarin speakers. (May 2021) - Lu, Yu-An; Lee-Kim, Sang-Im
Highlights: T3 [X 214 ] is shorter than T2 [X 35 ] and T1 [X 55 ] in Taiwan Mandarin (TM). T3 and T3half [X 21 ] are overestimated in duration judgments by TM listeners. The canonical representation of T3 evokes perceptual overestimation of its variants. The perception of vowel duration is partly guided by one's phonological knowledge. Abstract: Perceived vowel duration is known to be influenced by many factors, including f0 height/movement and ones' native phonological system. Using multiple experimental paradigms, this study examined whether native tonal representations and phonetic knowledge of duration associated with different lexical tones may further shape the ways in which vowel duration is perceived. In a perception experiment, Taiwan Mandarin and Korean listeners rated the duration of duration-controlled CV syllables carrying one of the four lexical tones in Mandarin or a reduced T3half (X 21 ). The results showed that perceived vowel duration by Korean listeners, the control group, reflected general perceptual biases: contour tones were rated as longer than level tones, and high- f0 tones were rated as longer than low- f0 tones. Taiwan Mandarin listeners, on the other hand, overestimated the duration of vowels carrying T3 (X 214 ) and T3half, despite their short phonetic duration in Taiwan Mandarin, indicating the significance of the canonical representation of the complex T3 contour. A spontaneous imitation experiment further supported the canonicity effect: T3half was again hyperarticulated, produced as longer and with similar f0 trajectories as T3full, based on its phonological association to T3. Taken together, the findings of the present study suggest that the perception of vowel duration is guided by higher-order phonological knowledge from speakers' linguistic experience as well as by general perceptual biases.